Climatology of atmospheric solar tidal mode effects on ionospheric F2 parameters over the American sector during solar minimum between cycles #23 and #24 - Santos, A. M.; Yang, G.; Pimenta, A. A.; Brum, C. G. M.; Batista, I. S.; Sobral, J. H. A.; Andrioli, V. F.; Batista, P. P.; Abdu, M. A.; Souza, J. R.; Manoharan, P. K.; Wang, C.; et al. (Frontiers in Astronomy and Space Sciences, 2024)
This work presents the contribution of solar atmospheric tides (diurnal, semidiurnal, and terdiurnal modes) to the variability of the parameters critical frequency (foF2) and peak height of the F2-layer (hmF2) in the American sector during the transition of solar cycles #23 and #24, a period considered one of the lowest solar activities of the modern era. The Digisonde data available in the GIRO data center were analyzed (12 stations), and the solar tide modes were evaluated regarding their amplitude, latitude, and seasonal dependence. The results showed that the hmF2 and foF2 strongly depend on latitude and seasonality, being more intense in the stations located in the south hemisphere. The same behavior is seen for the tidal amplitude fitted in these parameters, except for hmF2 diurnal tide, which is more intense at latitudes farther from the equator. Moreover, the seasonal variability of the amplitude of hmF2 in most cases presented an annual and semiannual component. A terannual component was also observed in 8h tide mode in the height and frequency parameters. Likewise, what was observed . in foF2, the variability in the mean amplitude and different modes of tides of hmF2 are higher over the sectors located in the southern hemisphere.